2009
DOI: 10.1177/0022034509351969
|View full text |Cite
|
Sign up to set email alerts
|

Strong Nanocomposites with Ca, PO4, and F Release for Caries Inhibition

Abstract: This article reviews recent studies on: (1) the synthesis of novel calcium phosphate and calcium fluoride nanoparticles and their incorporation into dental resins to develop nanocomposites; (2) the effects of key microstructural parameters on Ca, PO4, and F ion release from nanocomposites, including the effects of nanofiller volume fraction, particle size, and silanization; and (3) mechanical properties of nanocomposites, including water-aging effects, flexural strength, fracture toughness, and three-body wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 79 publications
0
102
0
5
Order By: Relevance
“…179 Replacing MCPM with less soluble DCP enhanced the strength but significantly reduced mineral ions release. 180 A study showed that by decreasing the particle size of DCP fillers to ~110 nm, the amount of mineral ions release can be significantly increased. 181 It has also confirmed that replacing DCP with silicon nitride whiskers enhanced the strength but at the expense of the mineral ion release.…”
Section: Composites Containing Ttcpsmentioning
confidence: 99%
“…179 Replacing MCPM with less soluble DCP enhanced the strength but significantly reduced mineral ions release. 180 A study showed that by decreasing the particle size of DCP fillers to ~110 nm, the amount of mineral ions release can be significantly increased. 181 It has also confirmed that replacing DCP with silicon nitride whiskers enhanced the strength but at the expense of the mineral ion release.…”
Section: Composites Containing Ttcpsmentioning
confidence: 99%
“…The addition of F, Ca or PO 4 nanoparticles may alter or improve the properties of nanocomposites. Xu et al 20 observed that composites containing CaF 2 nanoparticles had a 3-fold higher flexural strength than resin-modified glass ionomer. Other examples are nanocomposites containing nanoparticles of amorphous calcium phosphate, which had a 2-fold higher strength than an ordinary composite, reducing potential secondary caries and restoration fracture 21 , and silver-containing materials that improve the polymerisation process 22 .…”
Section: Nanotechnology and Dental Applicationsmentioning
confidence: 99%
“…Applications of nano-sized fillings in the resin matrices have overcome some of the mechanical limitations and have significantly improved their clinical performance. Commonly used nanomaterials include nano-ZnO, 3,4 nano-silica, 18,19 nano-calcium phosphate and calcium fluoride (nano-Ca 3 (PO 4 ) 2 and CaF 2 , respectively), 20 and nano-TiO 2 . 21 In addition to composite resins, the utilization of nanomaterials in dental adhesives has also effectively improved their bonding strengths and mechanical properties.…”
Section: Composite Resins and Bonding Systemsmentioning
confidence: 99%